The Influence of Diagnosis, Age, and Gender on Surgical Outcomes in Patients With Adult Spinal Deformity. Issue 8 (December 2018) - Ayhan, Selim; Yuksel, Selcen; Nabiyev, Vugar; Adhikari, Prashant; Villa-Casademunt, Alba; Pellise, Ferran; Perez-Grueso, Francisco Sanchez; Alanay, Ahmet; Obeid, Ibrahim; Kleinstueck, Frank; Acaroglu, Emre; ,
Study Design: Retrospective review of prospectively collected data from a multicentric database. Objectives: To determine the clinical impact of diagnosis, age, and gender on treatment outcomes in surgically treated adult spinal deformity (ASD) patients. Methods: A total of 199 surgical patients with a minimum follow-up of 1 year were included and analyzed for baseline characteristics. Patients were separated into 2 groups based on improvement in health-related quality of life (HRQOL) parameters by minimum clinically important difference. Statistics were used to analyze the effect of diagnosis, age, and gender on outcome measurements followed by a multivariate binary logistic regression model for these results with statistical significance. Results: Age was found to affect SF-36 PCS (Short From-36 Physical Component Summary) score significantly, with an odds ratio of 1.017 (unit by unit) of improving SF-36 PCS score on multivariate analysis ( P < .05). The breaking point in age for this effect was 37.5 years (AUC = 58.0, P = .05). A diagnosis of idiopathic deformity would increase the probability of improvement in Oswestry Disability Index (ODI) by a factor of 0.219 and in SF-36 PCS by 0.581 times ( P < .05). Gender was found not to have a significant effect on any of the HRQOL scores. Conclusions: Age, along with a diagnosis of degenerative deformity, may have positive effects on the likelihood of improvement in SF-36 PCS (for age) and ODI (for diagnosis) in surgically treated patients with ASD and the breaking point of this effect may be earlier than generally anticipated. Gender does not seem to affect results. These may be important in patient counseling for the anticipated outcomes of surgery.